UNTUKMU.COM : THE CROWDSOURCING APPLICATION TO LEVERAGING THE USED OF SECONDHAND GOODS - Yulyani Arifin; Syarifah Diana Permai; Herena Pudjihastuti; Kristian Dwiputra; Fiandra Rheza Faisal; Marcellino Marcellino (Social Economics and Ecology International Journal (SEEIJ), 2018)
Information technology can be used in profit or non-profit activities. The concept of crowdsourcing has been widely used in fundraising in the form of money, better known as crowdfunding. In general, most people has secondhand items that are still good to use by others. On the other hand, there are also many people who need those items but cannot afford to buy them. A Website application with the Crowdsourcing concept can be used to bring together donors with recipients of donations in the form of goods.This study conducted data collection to assess the needs of application through questionnaires and analyzed the data using descriptive statistical analysis and Chi Square independence tests, and then developed a website-based application untukmu.com.  This study examined the relationship between age, type of work and intention to donate and the type of goods needed. The Chi Square independence test showed that there is no relationship between age and type of work to the intention to donate.  The descriptive statistics analysis showed that the majority (82%) of the types of goods usually donated by the donors are clothing. The results of the analysis provides input for the development of the application Untukmu.com. In the last stage, the study evaluated the level of satisfaction of the users (i.e. the donors) based on the level of ease of using the application and the time needed to master the application. The analysis showed that there is no relationship between the ease of use of the application and the donors satisfaction,  but there is relationship between time needed to master the application to the user satisfaction. Untukmu.com application has a good usability level since users have no difficulty in using this application and are satisfied with the features available in the application.